Legal Aspects of Electronic Storage of Notarial Deed Minutes - Azza Baharuddin, Alief; Hanim, Lathifah (Jurnal Konstatering, 2025)
UUJN Amendment Article 1 Number 1 defines a notary as a public official who is authorized to make authentic deeds and has other authorities as referred to in this law or based on other laws. UUJN Amendment Article 16 paragraph (1) letter b states that in carrying out his/her position, a notary is required to make a deed in the form of minutes of the deed and store it as part of the notary protocol. The purpose of the study was to determine and analyze the legal aspects (regulations) of storing minutes of notary deeds electronically and to determine and analyze how to overcome data leaks of minutes of notary deeds stored electronically. The type of research is in the form of normative legal research with a statutory approach method supported by secondary data sources through library data collection and using a prescriptive analysis method. The results of the study are: (1) The legal aspects of storing minutes of notary deeds electronically are proven by the Notary Law not being able to keep up with technological developments that facilitate and provide security for notaries in carrying out their obligations, because there are no norms that regulate notaries so that they can store minutes of deeds electronically. (2) The method for dealing with leaks of notarial deed minutes data stored electronically is to scan the deed minutes file which is then stored on an external hard disk to accommodate the deed minutes document throughout the notary's term of office, create a special deed minutes storage server owned by the notary through the notary professional organization at each regional level and access to view notarial deed minutes stored electronically is only given to parties who have authority over the deed minutes such as notaries and the notary supervisory board which consists of government elements, notary elements and expert or academic elements.